2001
DOI: 10.1034/j.1600-0714.2001.300209.x
|View full text |Cite
|
Sign up to set email alerts
|

The secretion of parotid saliva as stimulated by 10% citric acid is not related to precipitating factors in burning mouth syndrome

Abstract: Burning mouth syndrome (BMS) is known to have multiple precipitating factors and exists in various clinical subtypes. If salivary gland function was compromised in BMS it could help explain the link with diverse precipitating factors. This study quantified stimulated right and left parotid flow rates (SPFR) in 114 patients with BMS. It also attempted to correlate SPFR with haematinic parameters, oral candidal carriage, concurrent drug therapy and BMS subtype. No relationship was found between haematinic parame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
14
0
6

Year Published

2004
2004
2014
2014

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 25 publications
4
14
0
6
Order By: Relevance
“…Moreover, salivary compositional changes unrelated to flow rate reduction, although not found in all the studies, have been associated with complaints of BMS as well. 2,5,10 These reports are fully in accord with our results as well as with the study recently reported by Lamey et al, 26 who also demonstrated salivary compositional changes with no concomitant significant flow rate reduction in the subjects complaining of BMS. Their results emphasize the possible role of salivary composition in the underlying mechanism of OSC, because it is wellknown that some of the salivary parameters analyzed (such as Na, Cl, K) are flow rate dependent, and one would have otherwise questioned the role of salivary composition as opposed to a possible role for salivary flow rate in the OSC patients.…”
Section: Discussionsupporting
confidence: 96%
See 1 more Smart Citation
“…Moreover, salivary compositional changes unrelated to flow rate reduction, although not found in all the studies, have been associated with complaints of BMS as well. 2,5,10 These reports are fully in accord with our results as well as with the study recently reported by Lamey et al, 26 who also demonstrated salivary compositional changes with no concomitant significant flow rate reduction in the subjects complaining of BMS. Their results emphasize the possible role of salivary composition in the underlying mechanism of OSC, because it is wellknown that some of the salivary parameters analyzed (such as Na, Cl, K) are flow rate dependent, and one would have otherwise questioned the role of salivary composition as opposed to a possible role for salivary flow rate in the OSC patients.…”
Section: Discussionsupporting
confidence: 96%
“…12,14,24 Hyposalivation and low perceived salivary flow (xerostomia) are significantly associated with dissatisfaction with tasting, 23 and although a reduced salivary flow in patients with BMS was reported in some of the studies, it was not demonstrated by others. 10,25,26 In this respect it is important to note various studies reported by Grushka et al [13][14][15][16][17] that showed that BMS was simultaneously and commonly accompanied by complaints of xerostomia and persistent or altered taste. In any case, the subjective sensations of dry and burning mouth appear to be a complex issue among the elderly population.…”
mentioning
confidence: 96%
“…So, reduced saliva secretion as a consequence of antidepressant medication has been widely reported (24), as dry mouth is a common adverse effect of antidepressants, such as selective serotonin reuptake inhibitors (SSRIs) (42). On the other hand, a higher frequency of Candida isolation from the oral cavity of patients under treatment with psychotropic drugs (64.7%) in relation to control individuals (33.3%) has been found (27).…”
Section: Discussionmentioning
confidence: 99%
“…[15][16][17] Kadınlarda gece idrara çıkma sıklığı arttıkça yanan ağız sendromu görülme sıklığının da arttığı belirtilmektedir. Ayrıca gece susayan ve içecek alan hastalarda da sendromun görülme sıklığı artmaktadır.…”
Section: Etiyolojiunclassified